Numerical Evaluation of Earthquake Effect on Cisumdawu Tunnel Stability - I Gde Budi Indrawan; Jutika Aditya Nugraha Nugraha; Dwikorita Karnawati (Geological Engineering Department Universitas Gadjah Mada, 2020)
Cisumdawu Tunnel is located approximately 3.95 km southeast of the activeLembang Fault. Earthquakes induced by movement of the the active the strike-slip fault may influence stability of the twin tunnel. This paper presents results of numerical analyses carried out to demonstrate effect of a worst-case scenario of earthquake load potentially induced by the Lembang Fault on the stability of the Cisumdawu Tunnel. Static and pseudo-static tunnel stability analyses were carried out at 11 observation stations of tunnel face mapping using RS2 finite element package (Rocscience, Inc.). In the pseudo-static analyses, a 0.48 horizontal seismic load coefficient, which was obtained from a deterministic seismic hazard analysis (DSHA) based on a 6.8 maximum magnitude of estimated earthquake sourced from the Lembang Fault using Campbell-Bozorgnia (2014) attenuation relationship, was applied to the finite element models. The numerical analysis results showed that strength factors of the rock masses around the twin tunnel were greater than unity, both under the static and earthquake loads. The forepolling zones, however, appeared to be under an overstressed condition. Reduction of rock strength factor around the tunnel roof due to application of the earthquake load occurred at all observation stations. Total displacement contours of rock masses around the twin tunnel indicated an increased rock mass displacement due to the earthquake load, as compared to that due to the static load. Under the static load, the largest displacement occurred at the tunnel inverts. The predicted roof displacements obtained from this study were in a reasonably good agreement with those obtained from the field measurements. Number of yielded elements and extend of shear and tension failure zones in the rock masses around the twin tunnel also appeared to increase due to the earthquake load. Despite slight tunnel displacement as predicted in the numerical analyses, the worst-case scenario of earthquake load potentially induced by the Lembang Fault may only cause failures of the rock masses around the Cisumdawu Tunnel. To prevent the twin tunnel displacement caused by such relatively severe earthquake loads, however, stabilizing surrounding the relatively poor ground condition may be necessary.